Unfolding Knowledge on Sexual Violence Experienced by Black Lesbian Survivors in the Townships of Cape Town, South Africa - Wilson, Jacqueline K. (European Journal of Social Science Education and Research, 2018)
Sexual violence is conceptualised as a hate or bias-motivated crime, and is recognised as a social problem of global proportion. However, the platform for this paper focuses on incidents of rape in South Africa, a country where the most progressive legislation concerning sexual minorities is enforced, including gender non-conforming people namely Lesbian, Gay, Bisexual, Trans and Intersex (LGBTI). South Africa still must address rape inflicted on black lesbians residing in Cape Town townships, despite gender equality being granted in on the basis of sexual orientation (Silvio, 2011). The same applies to same sex marriages, making South Africa the role model of other African countries yet to be included in the signatory to the 2008 United Nations Human Rights Council Resolution on Sexual Orientation and Gender Identity. An alternative concept to categorising rape as a hate crime might be a more effective tool in the legislation to combat rape based on sexual orientation; justice will be served as a female homosexual enjoys equal citizenship as that of a heterosexual citizen. Preliminary findings show that some rape victims became mothers as a result of the rape. Rape victims discuss conception due to corrective rape and how this affects the mother-child relationship. Feedback from victims include coping mechanisms from religious beliefs to alcohol abuse. None of the rape-survivors interviewed in this study contracted HIV/AIDS as a consequence of the rape.